Integrating Palliative Care and Heart Failure: the PalliatHeartSynthesis realist synthesis - Tracey McConnell; Carolyn Blair; Geoff Wong; Claire Duddy; Clare Howie; Loreena Hill; Joanne Reid (NIHR Journals Library, 2024)
Background Cardiovascular disease is the most common cause of death worldwide, highlighting the need for studies to determine options for palliative care within the management of patients with heart failure. Although there are promising examples of integrated palliative care and heart failure interventions, there is heterogeneity in terms of countries, healthcare settings, multidisciplinary team delivery, modes of delivery and intervention components. Hence, this review is vital to identify what works, for whom and in what circumstances when integrating palliative care and heart failure. Objectives To (1) develop a programme theory of why, for whom and in what contexts desired outcomes occur; and (2) use the programme theory to co-produce with stakeholders key implications to inform best practice and future research. Design A realist review of the literature underpinned by the Realist and Meta-narrative Evidence Syntheses: Evolving Standards quality and reporting standards. Data sources Searches of bibliographic databases were conducted in November 2021 using the following databases: EMBASE, MEDLINE, PsycInfo, AMED, HMIC and CINAHL. Further relevant documents were identified via alerts and the stakeholder group. Review methods Realist review is a theory-orientated and explanatory approach to the synthesis of evidence. A realist synthesis was used to synthesise the evidence as successful implementation of integrated palliative care and heart failure depends on the context and people involved. The realist synthesis followed Pawson's five iterative stages: (1) locating existing theories; (2) searching for evidence; (3) document selection; (4) extracting and organising data; and (5) synthesising the evidence and drawing conclusions. We recruited an international stakeholder group (n = 32), including National Health Service management, healthcare professionals involved in the delivery of palliative care and heart failure, policy and community groups, plus members of the public and patients, to advise and give us feedback throughout the project, along with Health Education England to disseminate findings. Results In total, 1768 documents were identified, of which 1076 met the inclusion criteria. This was narrowed down to 130 included documents based on the programme theory and discussions with stakeholders. Our realist analysis developed and refined 6 overarching context-mechanism-outcome configurations and 30 sub context-mechanism-outcome configurations. The realist synthesis of the literature and stakeholder feedback helped uncover key intervention strategies most likely to support integration of palliative care into heart failure management. These included protected time for evidence-based palliative care education and choice of educational setting (e.g. online, face to face or hybrid), and the importance of increased awareness of the benefits of palliative care as key intervention strategies, the emotive and intellectual need for integrating palliative care and heart failure via credible champions, seeing direct patient benefit, and prioritising palliative care and heart failure guidelines in practice. The implications of our findings are further outlined in the capability, opportunity, motivation, behaviour model. Limitations The realist approach to analysis means that findings are based on our interpretation of the data. Future work Future work should use the implications to initiate and optimise palliative care in heart failure management. Conclusion Ongoing refinement of the programme theory at each stakeholder meeting allowed us to co-produce implications. These implications outline the required steps to ensure the core components and determinants of behaviour are in place so that all key players have the capacity, opportunity and motivation to integrate palliative care into heart failure management. Study registration This study is registered as PROSPERO CRD42021240185. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR131800) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 34. See the NIHR Funding and Awards website for further award information. Plain language summary People with heart failure can frequently become unwell with poor quality of life despite advanced medical therapies. Palliative care can do much to alleviate suffering for people with heart failure as it focuses on adding to patient care by treating the whole person - their physical, psychosocial and spiritual needs, which improves quality of life for both the patient and their loved ones. However, poor integration of palliative care into the management of heart failure is an ongoing problem. To understand why this is, we have undertaken a particular method of literature review called realist synthesis that looks at all types of literature to identify what works, for whom and in what circumstances. We have worked closely with our stakeholder group (including healthcare providers and patients who have heart failure and their carers) to advise and give us feedback throughout this review. We found the following: A review of education for health and social care professionals is needed to make sure that palliative care for patients with non-cancer conditions such as heart failure is adequately covered. Education is also needed for patients and those who care for them to help them understand what palliative care is (holistic care delivered alongside active heart failure management based on patient need) and what it is not (only for cancer patients and end-of-life care). All health and social care staff should work closely together when managing patients with heart failure to learn from each other. Policy, practice and service user champions must be identified and supported to share the benefits of integrated care. Visible guidelines should prioritise integrated palliative care and heart failure so they become part of everyday practice. Scientific summary Background Cardiovascular disease is the most common cause of death worldwide and the most frequent cause of hospitalisation among individuals aged > 65 years. In 2012, heart failure (HF) was estimated to account for £22.5B of health expenditure globally; between 2012 and 2030 it is estimated that total costs will increase by 127%. Integrating palliative care (PC) with routine management of HF has been shown to significantly reduce healthcare costs overall compared to usual care (without PC) and significantly reduces the number of hospital visits and duration of inpatient stays. There is evidence of improved patient and informal caregiver outcomes when PC is integrated in HF management. Integrated palliative and HF care aims to achieve continuity of care by integrating administrative, organisational, and clinical services that make up the patients care network. However, two decades have passed since the first publication on the benefits of PC for patients with HF. The scarcity of effective integration of PC into HF management can be explained by a number of factors, including uncertainty around the HF disease trajectory and complexities of communicating this uncertainty to the patient and family members. The 2021 European Society of Cardiology (ESC) Guidelines for the diagnosis and treatment of acute and chronic HF highlighted the need for studies to determine specific options for PC within the treatment of HF. Although we have some promising examples of integrated PC and HF interventions, there is heterogeneity in terms of countries, healthcare settings, delivery and intervention components. Hence, this review is vital for identifying what works best, for whom and in what circumstances. Aim and objectives To understand how integrated PC and HF interventions work in different healthcare settings for example inpatient/outpatient, and for which groups of people, so we can recommend strategies to maximise the potential for widespread implementation, reduce healthcare costs, and improve quality of life (QoL) for patients and informal carers. To conduct a realist synthesis (RS) to build an understanding of which integrated PC and HF interventions work best together, in which contexts and for which patients who have HF and informal carers.